Comparison Of Education Policies In Indonesia And Finland As Well As The Implementation Of The Concept Of Multiculturalism In Historical Learning - Azmi, Inez Kalyana (History Education, University of Jember, 2024)
This article seeks to analyze education policy in Indonesia and make an in-depth comparison on the aspects of curriculum, human resource management, and infrastructure as well as its relation to the implementation of the concept of multiculturalism in history learning. Furthermore, this article describes the educational policies used in Indonesia and the problems that occur. Then the researcher compares it with the education policy in Finland, which is included in the category of countries with the best quality of education in the world. Based on this, the research problems can be formulated as follows: (1) how is the education policy in Finland?, (2) how is the education policy in Indonesia?, (3) how is the difference between education policy in Indonesia and Finland?, (4) how is the implementation of multiculturalism in history learning?. As for the collection of data sources, researchers use literature sources by conducting literature reviews from relevant scientific sources and then analyzed using simple and communicative sentences for easy understanding. The purposes of writing this article are: (1) to fulfill the requirements of the History of International Relations course assignment, (2) to know the comparison of education policies in Indonesia and Finland, (3) to understand multicultural education and the implementation of multiculturalism in history learning, (4) to be used as reference material for Indonesia to further improve the quality of education by transforming education policies that are tailored to the characteristics, opportunities, and challenges of existing education and can adopt policies enacted by the country of Finalndia which has proven successful in improving education in its own country.